2011
DOI: 10.1111/j.1654-109x.2011.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Traits and growth of liana regeneration in primary and secondary forests of Central Amazonia

Abstract: Question: Do traits of liana regeneration differ among secondary forest types of varying land‐use history and primary forest? Location: Eighty kilometers north of Manaus, Brazil. Methods: We compared plant functional traits and growth rates of liana regeneration (<1.7‐m length) among two secondary forest types and primary forest. Secondary forest types were: Vismia (on land formerly clear‐cut, used for pasture and intensively burned) and Cecropia (no pasture usage or intensive fires after clear‐cut). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…; Carrasco‐Urra & Gianoli ; Roeder et al. ), and there is also evidence pointing to a complementary role between tree/shrub species identity and trellis availability (Garbin et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Carrasco‐Urra & Gianoli ; Roeder et al. ), and there is also evidence pointing to a complementary role between tree/shrub species identity and trellis availability (Garbin et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Climbing strategies differ during succession, with a higher proportion of stem twiners present in early successional stages as compared to tendril climbers (Letcher & Chazdon ), but other traits, such as leaf size and plant length, may become important during succession (Roeder et al. ). Moreover, stem twiners are less favoured by the presence of trees with larger trunk diameter (Carrasco‐Urra & Gianoli ).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetative propagation capacity may also be an important biological factor, because clonality increases the local abundance of individuals, especially after natural or anthropogenic disturbances (Ledo & Schnitzer 2014, Roeder et al . 2012). In many plant species, vegetative reproduction may have a greater effect on local and regional abundance than seed reproduction, and is thus considered an important predictor of species abundance (Herben et al .…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of liana (woody climber) community structure that can be affected by natural or anthropogenic forest disturbance include the aggregation of individuals or age structuring in a liana community (Ledo & Schnitzer 2014, Roeder et al . 2012, Schnitzer et al . 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, this does not mean that all liana species are shade-intolerant (Gianoli et al 2010), and in fact they appear to show different shade-tolerance levels (Gilbert et al 2006). It has been suggested that with the increase of disturbances, light-demanding liana species might benefit (Roeder et al 2012), while shade-tolerant species may decrease. In addition, a density increase of shade-tolerant species is expected when a decrease in disturbance occurs and the forest understorey becomes darker.…”
Section: Introductionmentioning
confidence: 99%